Analisis Kandungan Ion Flourida pada Sampel Air Tanah dan Air PAM Secara Spektrofotometri - Astriningrum, Yodifta; Suryadi, Herman; Azizahwati, Azizahwati (Majalah Ilmu Kefarmasian, 2010)
Fluoride ion is one of the compounds that are known to have benefits in the prevention of dental caries when used in certain concentrations, but also hasnegative effects that may cause the occurrence of dental and bone fluorosis when the intake was in excessive concentration. One of the fluoride intakes comes fromwater that is consumed. The aim of this research was to identify and measurefluoride ion levels in groundwater and piped water that used as drinking water consumption in the community. Measurement of fluoride ion concentration isdone by using visible spectrophotometry at the maximum wavelength of 586 nmusing the sodium 2-parasulfophenylazo 1,8-dihydroxy-naphthalene-3,6disulfonate (SPADNS)-zirconil acid reagent. This method was optimized by thesearch of range of absorption which stable for 10 minutes after reagent addition.The limit of detection, limit of quantitation, and coefficient of variation forfluoride ion were 0.0452 mg/L, 0.1506 mg/L, and 0,63%, respectively. While therecovery of fluoride ion in sample were in the range of 90,50-102,04%. The measurement results of the samples showed levels of fluoride ions in groundwaterand piped water varied between 0.05 to 0.78 mg/L. This range was still within allowed levels according the rules of Indonesian health ministers No.492/MENKES/PER/IV/2010 where the maximum allowable fluoride concentration is 1.5 mg/L.